Government accountability in Iraq: parliamentary investigation in the Iraqi Council of Representatives / Taghreed Abdul Qadir Ali and Faridah Jalil - Abdul Qadir Ali, Taghreed; Jalil, Dr. Faridah (2014)
A parliamentary investigation defines a legal process initiated against the prime minister, ministers, and government officials to ensure the transparency and integrity of government and all its associated bodies. The lack of effectiveness of investigation and oversight function of the Iraqi Council of Representatives in government accountability was one of the main reasons for investigation failure to many government scandals and corruption in the government. The aim of this study is to identify the requirements for providing a legal power to the Council of Representatives in order to investigate and oversight the government and achieve government accountability, and to determine current obstacles those hinder the work of investigation and oversight committees as well as the causes of inability of Iraqi legislators in improving the constitution and empowering the assigned committees for government accountability. The main problem that will be discussed in this study is the inability of the council of representatives of Iraq to secure government accountability through investigation and oversight missions. The result is that the internal process is completely ineffective for government accountability, additionally the current assigned committees are unable to practice their rights and oversight the government officials and Prime Minister, ministers, and government officials. The contribution of this study is through the reinforcement of the role and responsibilities of the Iraqi Representatives in the Council for the benefit and interest of the Iraqi people by protecting the national economy from corruption and wasting national wealth.